ANALYSIS DIGITAL PARENTING BEHAVIOR IN THE CONTEXT OF LIFELONG LEARNING FOR PARENTS OF TEENAGE CHILDREN - Afra Shafa Ramadlani; Joni Rahmat Pramudia; Yanti Shantini (Sean Institute, 2023)
This article aims to analyze digital parenting behavior in the context of lifelong learning for parents of teenagers. The method used a literature study to collect and analyze related research results. The analysis concludes that the digital era brings both benefits and challenges for parents in educating their children. Children are exposed to digital tools that can sometimes cause negative impacts such as excessive screen use and addiction. However, parents can adapt their parenting by monitoring their children's use of digital devices, setting appropriate limits, and communicating effectively with their children. Lifelong learning is also important for parents, as they can use digital tools to access information and resources to improve their parenting skills. It is important for parents to be aware of the risks and benefits of technology and actively engage in lifelong learning to ensure the healthy development of their children in the digital age.